SUFFERING AND PERSEVERANCE IN REVELATION: A THEOLOGY OF HOPE FOR THE CHURCH IN THE MIDST OF CRISIS - Juni Balle; Anselma Sibero; Adi Prasetyo Wibowo (CV Naskah Aceh, 2026)
This article examines the meaning of suffering and perseverance in the Book of Revelation within the framework of a theology of hope for the church amid crisis. The study focuses on the experience of suffering among early Christian communities as reflected in the apocalyptic narrative of Revelation, as well as the call to perseverance (hypomonē) as a faithful response of faith. The theological approach integrates historical-contextual analysis and biblical theological reflection, particularly in understanding the socio-political background of the Roman Empire, likely during the reign of Domitian. Through exegetical analysis of key passages, this article argues that suffering in Revelation is not portrayed as a sign of defeat for the people of God but as participation in the victory of the Lamb. By considering contemporary crises—including social pressure, injustice, and religious marginalization—the article further explores how Revelation's theology of hope can shape a resilient and witnessing church today. Thus, this study contributes to the development of a transformative and contextually relevant theology of hope for the contemporary church.